Laparoscopic Ureteroureterostomy vs. Common Sheath Ureteral Reimplantation in Children With Duplex Kidney Anomalies - Gerwinn, Tim; Gnannt, Ralph; Weber, Daniel M.; Gobet, Rita; Mazzone, Luca (Frontiers in Pediatrics, 2021)
Purpose: Laparoscopic ureteroureterostomy (LUU) has been proposed as an alternative to common sheath ureteral reimplantation (CSUR) in children with symptomatic duplex kidneys. However, data is limited for LUU in the pediatric population. The aim of this study was to analyze our experience with LUU and to compare the results with those after CSUR to assess whether a less invasive surgical approach could be a valid alternative. Patients and methods: The data of all children with duplex kidneys who underwent either LUU or CSUR at our center from 2006 to 2018 were reviewed retrospectively. After parental counseling, the option of LUU was provided as an alternative to CSUR for unilateral procedures and in the absence of vesicoureteral reflux to the receiving ureter. Baseline characteristics, indication for surgery, hospitalization and operative times, and intraoperative, post-operative, and late complications were analyzed. Preoperative and 1-year post-operative sonographies were reviewed by a pediatric radiologist. Increasing renal pelvic diameter (Δ >5 mm) was regarded as a sign of ureteral obstruction. Results: Forty children were included in this study, with 16 children receiving LUU and 24 children receiving CSUR. The children had a mean age of 2.7 years (7 months−9.8 years) and were followed up in our outpatient clinic for an average of 3.9 years (3 months−10.6 years) after surgery. The median hospital stay was 2 days shorter after LUU. Initially, a considerably longer time was needed for LUU, but after more experience was gained, similar operative times were observed for both procedures. Complications were encountered in both groups. After LUU, two patients developed anastomotic leakage: one was managed conservatively, and one required temporary nephrostomy. In the CSUR group, one patient developed vesicoureteral obstruction during follow-up and required reoperation with LUU. The occurrence of post-operative urinary tract infections was similar in both groups. No complications related to the ureteral stump after LUU arose. Conclusion: LUU is a safe and efficacious treatment option for children with duplex kidney anomalies and can be used as an alternative to CSUR. All children receiving LUU showed a non-obstructive, patent anastomosis and no signs for stenotic compromise of the receiving ureter.